A small molecule chaperone rescues the stability and activity of a cancer‐associated variant of NAD(P)H:quinone oxidoreductase 1 in vitro. Issue 3 (30th October 2019) - Strandback, Emilia; Lienhart, Wolf‐Dieter; Hromic‐Jahjefendic, Altijana; Bourgeois, Benjamin; Högler, Anja; Waltenstorfer, Daniel; Winkler, Andreas; Zangger, Klaus; Madl, Tobias; Gruber, Karl; Macheroux, Peter
Abstract : Abstract : NAD(P)H:quinone oxidoreductase 1 (NQO1) is a human FAD‐dependent enzyme that plays a crucial role in the antioxidant defense system. A naturally occurring single‐nucleotide polymorphism ( NQO1*2 ) in the NQO1 gene leads to an amino acid substitution (P187S), which severely compromises the activity and stability of the enzyme. The NQO1*2 genotype has been linked to a higher risk for several types of cancer and poor survival rate after anthracycline‐based chemotherapy. In this study, we show that a small molecular chaperone (N‐(2‐bromophenyl)pyrrolidine‐1‐sulfonamide) repopulates the native wild‐type conformation. As a consequence of the stabilizing effect, the enzymatic activity of the P187S variant protein is strongly improved in the presence of the molecular chaperone in vitro .